Perencanaan Fasilitas Pengelolahan Limbah Sewage pada KMP. Takabonerate - Saleh, Azwar; Sitepu, Andi Husni; Baharuddin, Baharuddin (Jurnal Riset & Teknologi Terapan Kemaritiman, 2022)
KMP. Takabonerate is a Ro-Ro ferry operated by PT. ASDP Indonesia Ferry Selayar. This ship is classified as a non-conventional class ship with the SM Class mark, which means that technically this ship is built with mechanical and electrical installations in full compliance with BKI requirements. One disadvantage of the group of non-convention vessels is not obliged to install sewage water treatment onboard. These conditions can lead to potential pollution and environmental damage. International Maritime Organization (IMO) has agreed on rules for handling sewage waste through MARPOL which has been adopted by the government through presidential regulations and ministerial regulations to be enforced, namely Annex IV 11 regulation which states that sewage waste can be disposed of within 12 miles of the nearest coastline to untreated waste and 3 miles from the nearest shoreline for waste that has been treated and meets the technical specifications of MARPOL. Therefore, this research was conducted to design a sewage treatment plant at KMP. Takabonerate, the old sewage tank is replaced by waste treatment plant sewage can serve a total passenger of 283 people with a minimum capacity of 2,83m3 with counted the dimensions and weight of sewage waste processing equipment. From the results of the selection, it was decided that the Omnipure 6440 waste treatment equipment with the electroflotation treatment method had a capacity of 1684,62 litres per hour. After selecting the equipment, the piping system is designed for the operation of the waste treatment equipment based on the applicable class regulations.